The Roles of Persis in Education Development in Indonesia 1923-2024 - Samsudin, Samsudin; Sudana, Djodjo Sukardjo; Suwanda, Satya Adilaga (UIN Sunan Gunung Djati Bandung, 2024)
Persis (Persatuan Islam –Islamic Union) is one of the Islamic organizations in Indonesia that has made a significant contribution to the development of education since it was founded in 1923. This article aims to analyze the role of Persis in building an education system based on Islamic values, starting from the colonial era and the independence to the current modern era. Using a historical and qualitative-descriptive approach, this research examines the educational strategies, challenges and innovations carried out by Persis through madrasas, Islamic boarding schools and formal educational institutions. The findings show that Persis is consistent in fighting for education based on pure Islamic beliefs, both through curriculum formation, teacher training and the development of educational institutions. In the reform and digital era, Persis continues to adapt to technology and global needs to ensure the relevance of Islamic education in producing a generation with noble character and high competence. This research confirms that the role of Persis education does not only cover the Islamic realm but also contributes to Indonesia's national development. Contribution: By promoting character education through various community initiatives, including social media outreach, Persis demonstrates its commitment to fostering a generation that embodies noble values while being equipped for modern societal roles.